The influence of a phytobiotic with F. ulmaria extract and lactobacilli on the clinical and physiological status of calves - A. A. Ivanovsky (Аграрная наука Евро-Северо-Востока, 2024)
Purpose of the research: to study the effect of a phytobiotic additive on some clinical and physiological parameters of the body of calves during the dairy period (biochemical and morphological blood parameters, live weight gain and disease resistance). The subject of the study was a phytobiotic with the code name Fitostim, which is based on an extract of meadow-sweet (Filipendula ulmaria (L.) Maxim.) and a lyophilized culture of lactic acid microorganisms. The experiment used Holstein calves, divided into experimental (Fitostim + traditional diet) and control (traditional diet) groups of 12 animals each. Starting from 4 days of age, calves in the experimental group were administered Fitostim daily, individually, orally for 30 days at a dose of 3 grams per head, after dilution in milk. Blood tests for morphological (erythrocytes, leukocytes, hemoglobin, leukoformula) and biochemical parameters (IgG, total protein, albumin, ALT, AST, creatinine) were carried out on the 10th and 30th days of the experiment. By the end of the experiment, in the experimental group of calves, compared with the control, there was an increase in ALT (8.0±0.01 units/l) by 19.4 %, total protein (51.4±0.07 g/l) by 14.7 %, albumin (44.0±0.01 g/l) by 15.4 %, creatinine (41.5±0.001 µmol/l) by 10.9 %, immunoglobulin G (5.9±0.01g /l) by 18 %, leukocytes (7.1±0.02×109/l) by 31 %. The studied morphological blood parameters (leukocytes, erythrocytes, hemoglobin, leukoformula) did not go beyond the reference values. Recovery from enteritis in calves in the experimental group occurred earlier by 1.8±0.3 days than in calves in the control group. Safety of calves is 100 %. The average daily increase in body weight in calves in the experimental group was 0.811±0.12 kg, which was 17.1 % higher than the result in the control.